Religions in practice an approach to the anthropology of religion - Bowen, John Richard 1951- (Boston Pearson, 2004)
A textbook for a course in anthropology or comparative religion looking at how people engage in the broad range of activities that invoke realities and powers beyond the reach of ordinary sense. The third edition incorporates topics that have come to the fore after 9- 11, more material on modern witchcraft, and other changes.
Preface -- 1. Studying religion through practice -- What is "religion"? -- An anthropological approach to religion -- Practices, contexts, diversity -- 2. Social theory in the anthropology of religion -- Religion as intellectual activity -- Religions in social life -- The psychology of religion -- 3. Ideas and practices of "religion" in Europe and elsewhere -- Western ideas of religion -- Other religions, other models -- Combining religious practices in Japan -- 4. Ritual and the shaping of emotions -- Rites of passage -- Initiation, secrecy, and fear -- Death ritual and the social order -- Grief and ritual form -- 5. Gender, religion, and ethnography -- Creating gender through ritual -- Reanalyses through the lens of gender -- Articulating women's perspectives through spirits -- Religious patriarchy and its challenges -- Women and Islamic dress -- 6. Patterns, powers, and the self -- Magic, patterns, and causes -- Explaining misfortune -- The New Age -- Wicca or modern witchcraft -- 7. Healing through religion -- Prayer, faith, and healing -- Narratives and pain relief -- Trance, possession and healing -- Modern magic in Japanese new religions. 8. Sorcery, witchcraft and modernity -- La Sorcellerie in Cameroon -- Azande oracles -- Sorcery and modernity -- Witchcraft as Satan versus God -- 9. Objects, images, and worship -- Conveying meaning through symbols -- masks in West Africa -- Images and offerings in Hinduism -- Relics and images in catholicism -- Mary and Marys in European societies -- 10. Crossing cultural boundaries -- Converting -- Translating : Mary in the Americas -- Adapting : Islamic sacrifice in new cultures -- 11. Sacred speech and divine power -- The Qur'an as recitation of God's speech -- The creative power of Navajo speech and song -- Speech and grace in protestant churches -- Religion on the web -- 12. Pilgrimages and places -- Centers and directions -- Dimensions of pilgrimage -- The pilgrimage to Mecca -- Contrasts in pilgrimage from Japan and India -- 13. Saints, visions, and prophets -- Saints as exemplars and as source of assistance -- Prophets and social change -- Revitalization movements : messiahs, millennia, and revivals -- Mormon prophecy and authority -- Muhammad and his successors -- 14. Religion, violence, and war -- Cults, sects, and violence -- Struggle and authority in Islam -- 15. The place of religions in modern nation-states -- Religious nationalisms -- Religion and state law -- Religious minorities and public religions -- Minority religions in Europe : toleration or public recognition? Religion, nation, and state in the United States -- Religion and public life.
Keywords: Religion; Religions; Ethnology -- Religious aspects